Functional knockdown of VCAM-1 at the posttranslational level with ER retained antibodies - Strebe, Nina; Guse, Annika (Journal of immunological methods, 2008)
Vascular cell adhesion molecule 1 (VCAM-1) is involved in the recruitment of leukocytes to inflammatory sites. In this study we present the first functional knockdown of VCAM-1 using an ER retained antibody construct. We generated a knockdown construct encoding the VCAM-1 specific single chain variable fragment scFv6C7.1 fused to the C-terminal ER retention sequence KDEL. HEK-293:VCAM-YFP cells stably expressing a VCAM-YFP fusion protein were transiently transfected with the knockdown construct and showed down-regulation of surface VCAM-1. Knockdown efficiency of the system is time-dependent due to used transient transfection of the intrabody construct. Furthermore, intrabody mediated knockdown of HEK-293:VCAM-YFP cells also impaired cell-cell interaction with Jurkat cells that are endogenously expressing VLA-4, the physiological partner of VCAM-1. Posttranslational knockdown with ER retained antibodies seems to be a promising technique, as shown here for VCAM-1.